2021
DOI: 10.1038/s41598-021-85415-y
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic roles of Wnt modulators R-spondin2 and R-spondin3 in craniofacial morphogenesis and dental development

Abstract: Wnt signaling plays a critical role in craniofacial patterning, as well as tooth and bone development. Rspo2 and Rspo3 are key regulators of Wnt signaling. However, their coordinated function and relative requirement in craniofacial development and odontogensis are poorly understood. We showed that in zebrafish rspo2 and rspo3 are both expressed in osteoprogenitors in the embryonic craniofacial skeleton. This is in contrast to mouse development, where Rspo3 is expressed in osteoprogenitors while Rspo2 expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 46 publications
(33 reference statements)
0
16
0
Order By: Relevance
“…We have recently reported that Rspo3 is expressed in osteoprogenitors in the craniofacial complex (33) 35 in both mice and zebrafish. However, rspo3 disruption in zebrafish has only mild effects on larval 36 craniofacial cartilage skeleton (33) and in mice its haplo-insufficiency does not appear to affect 37 craniofacial development. Human GWA studies have shown that RSPO3 might be specifically involved 38 in bone metabolism due to the strong association between RSPO3 common variants and bone mineral 39 density (34,35,(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently reported that Rspo3 is expressed in osteoprogenitors in the craniofacial complex (33) 35 in both mice and zebrafish. However, rspo3 disruption in zebrafish has only mild effects on larval 36 craniofacial cartilage skeleton (33) and in mice its haplo-insufficiency does not appear to affect 37 craniofacial development. Human GWA studies have shown that RSPO3 might be specifically involved 38 in bone metabolism due to the strong association between RSPO3 common variants and bone mineral 39 density (34,35,(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…Although all Rspos are expressed in bone during development, they appear to have specific functions and their deletion in mice and human leads to different phenotypes (10,13,(24)(25)(26)(27)(28)(29)(30)(31). Within the Rspo family, Rspo3 is of particular interest for bone because it is highly expressed in skeletal elements during mouse development (32,33) and several human GWA studies have shown that RSPO3 SNPs are strongly associated with bone mineral density and risk of fracture (34)(35)(36)(37)(38)(39). Not surprisingly, in vitro studies have shown that overexpression of, or treatment with, Rspos can enhance Wnt-ligand mediated osteoblast (OB) differentiation (10,28,40).…”
Section: Introductionmentioning
confidence: 99%
“…A recent paper has shown that rspo2 and rspo3 have overlapping activities in craniofacial development in fish [22]. To uncover the roles of Rspo2 and Rspo3 in mice that were potentially masked by an overlap in their functions, we inactivated both genes in the craniofacial mesenchyme in Wnt1-Cre;Rspo2 −/− ;Rspo3 fl/− mutants (Rspo2 KO ;Rspo3 NCKO ).…”
Section: Simultaneous Inactivation Of Rspo2 and Rspo3 Leads To Severe Disruption Of Craniofacial Development Including Odontogenesismentioning
confidence: 99%
“…The current study also provides the first description of the phenotypic consequences from the simultaneous loss of Rspo2 and Rspo3 during craniofacial development in mammals. A recent publication showed that Rspo2 and Rspo3 synergistically regulated craniofacial and dental development in fish [22]. However, they found significant differences between fish and mice in the expression patterns of the two Rspo genes, which made it important to examine mouse mutants.…”
Section: Simultaneous Inactivation Of Rspo2 and Rspo3 Leads To Severe Disruption Of Craniofacial Development Including Odontogenesismentioning
confidence: 99%
See 1 more Smart Citation